Evaluation of raw and processed full-fat soybeans for high-producing dairy cows - G.M. Ward; J.L. Morrill; M.B. Morrill; A.D. Dayton (Kansas Agricultural Experiment Station Research Reports, 1984)
Rations containing either soybean meal, raw full-fat soybeans, or processed soybeans were compared using 36 high-producing dairy cows in early lactation. The processed soybeans were heated in a California Pellet Milt Jet-Sploder for sufficient time (about 1 min) to produce beans with exit temperature of 340°F. The raw soybeans and heated soybeans were rolled before being"¢ mixed into the concentrate mixture. Alfalfa hay and concentrate were consumed ad libitum in a ratio of 35 % hay and 65 % concentrate. Milk production and percent protein in milk were significantly greater when cows were fed soybean meal or Jet-Sploded beans than when fed raw soybeans. Percent milkfat and total milk solids were not affected by treatment.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Soybeans; Milk production; Protein